Loss of α-1,2-mannosidase MAN1C1 promotes tumorigenesis of intrahepatic cholangiocarcinoma through enhancing CD133-FIP200 interaction - Wei, Yuanyan; Chen, Qihang; Chen, Jiayue; Zhou, Chenhao; Geng, Shuting; Shi, Danfang; Huang, Sijing; Liang, Zhiwei; Chen, Xiaoning; Ren, Ning; Jiang, Jianhai (Cell reports (Cambridge), 2023)
CD133 is widely used as a marker to isolate tumor-initiating cells in many types of cancers. The structure of N-glycan on CD133 is altered during the differentiation of tumor-initiating cells. However, the relationship between CD133 N-glycosylation and stem cell characteristics remains elusive. Here, we found that the level of α-1,2-mannosylated CD133 was associated with the level of stemness genes in intrahepatic cholangiocarcinoma (iCCA) tissues. α-1,2-mannosylated CD133+ cells possessed the characteristics of tumor-initiating cells. The loss of the Golgi α-mannosidase I coding gene MAN1C1 resulted in the formation of α-1,2-mannosylated CD133 in iCCA-initiating cells. Mechanistically, α-1,2-mannosylation promoted the cytoplasmic distribution of CD133 and enhanced the interaction between CD133 and the autophagy gene FIP200, subsequently promoting the tumorigenesis of α-1,2-mannosylated CD133+ cells. Analysis of iCCA samples showed that the level of cytoplasmic CD133 was associated with poor iCCA prognosis. Collectively, α-1,2-mannosylated CD133 is a functional marker of iCCA-initiating cells. [Display omitted] •α-1,2-mannosylated CD133 is associated with stemness in iCCA tissues•α-1,2-mannosylated CD133+ cells possess the characteristics of TICs•α-1,2-mannosylation promotes the tumorigenesis of iCCA-initiating cells•High level of α-1,2-mannosylation is associated with iCCA poor prognosis Wei et al. confirm that α-1,2-mannosylation of CD133 is a functional marker of iCCA-initiating cells. These findings provide the relationship between the N-glycan structure of CD133 and the characteristics of stem cells and provide a new strategy to eliminate iCCA-initiating cells.